The Future of Freedom of Press in Indonesia After the Personal Data Protection Law Era - Sumarwan, Untung; Hidayat, Arief; ALW, Lita Tyesta (UI Scholars Hub, 2023)
The press is a manifestation of the sovereignty of the Indonesian people. Unfortunately, the spirit of freedom of the press seems to be still experiencing shocks from various angles, one of which is the birth of Law number 27 of 2022 concerning Personal Data Protection (PDP Law). On the one hand, the presence of the PDP Law should be appreciated as a form of government effort to protect citizens' rights to privacy. However, unfortunately, several article provisions in the PDP Law still intersect with the Press, which are not a form of restriction in positive terms but have the potential for criminalization. One of the weaknesses of this law regarding press freedom, for example, is that the PDP Law does not provide exceptions for using personal data for public purposes. This certainly narrows the working space of the press, especially in uncovering cases or crimes committed by public officials. This paper explains how the PDP Law only focuses on efforts to protect privacy but does not look further into other aspects that can intersect and impact it, such as how personal data and privacy are linked in the journalistic realm. Furthermore, several articles in the PDP Law can further hinder the press from working. First, this arrangement does not exclude personal data from investigations conducted by the press, both specific and general personal data. The non-ideal arrangement in the PDP Law can cause problems in its implementation practices, especially concerning the function of the press in Indonesia. For this reason, it is necessary to amend the provisions in the Press Law to guarantee press freedom in the future.